2014
DOI: 10.7763/ijiet.2014.v4.364
|View full text |Cite
|
Sign up to set email alerts
|

How do Managers Regard Job Applicants with Online Degrees? Evidence from Turkey

Abstract: Abstract-This study addresses the debate on whether job applicants with online bachelor degrees would be perceived to be equals of those with traditional bachelor degrees; and whether the nature of the degree has an impact on the hiring decision of managers. We focus on bachelor's degrees earned on line due to the fact that hybrid education is not being delivered prevalently. In this respect, data were gathered from 20 managers working in various sectors who have an impact on the hiring process of job applican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Erden and Tekarslan (2014), who conducted a study in Turkey, concluded that on-line degree graduates were inferior to those earning degrees via the traditional method. They dismissed on-line graduates as inferior “due to their learner-centred and computer-based nature” (p. 3) devoid of the physical interactiveness engendered by traditional programmes.…”
Section: On-line Versus Traditional Degree Graduates’ Prospectsmentioning
confidence: 99%
See 3 more Smart Citations
“…Erden and Tekarslan (2014), who conducted a study in Turkey, concluded that on-line degree graduates were inferior to those earning degrees via the traditional method. They dismissed on-line graduates as inferior “due to their learner-centred and computer-based nature” (p. 3) devoid of the physical interactiveness engendered by traditional programmes.…”
Section: On-line Versus Traditional Degree Graduates’ Prospectsmentioning
confidence: 99%
“…Moreover, BestBizSchools (Grossman and Johnson, 2017) argues that there are more than 200 business accredited HLIs in the USA that offer on-line programmes. In Turkey, Erden and Tekarslan’s (2014) report predicted that 10 million Turks would engage in on-line learning in the subsequent decade. A recent article by the University World News (2019) also claims that “enrolments in on-line courses continue to grow by around 35% per annum as more and more higher education institutions deliver on-line degrees”.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, they noted that these studies rely on a hypothetical: what would employers do? Erden and Tekarslan (2014) asked a similar question regarding employer intent, but in a different geographical context. In examining Turkish employers' perceptions of degrees earned online, they provided additional evidence of latent employer bias.…”
Section: Employer Perceptions Of Online Learningmentioning
confidence: 99%